2020
DOI: 10.1111/apt.15885
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement project identifies factors associated with delay in IBD diagnosis

Abstract: Background: Delay in the diagnosis of inflammatory bowel disease (IBD) is common and contemporary UK studies are lacking. Aim: To determine factors associated with, and the consequences of, a prolonged time to diagnosis in IBD. Methods: This quality improvement study included 304 adults with a new IBD diagnosis made between January 2014 and December 2017 across 49 general practices (GP) and gastroenterology secondary care services. Outcome measures were demographic, clinical and laboratory factors associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 27 publications
(36 reference statements)
1
40
0
Order By: Relevance
“…Delay in diagnosis is more common in CD than UC (median delay, 7.6 months; interquartile range [IQR], 3.1-15.0 months and 3.3 months; IQR, 1.9-7.3 months, respectively; P < .001). 24 Data from the Swiss IBD cohort demonstrate that CD diagnosis can be delayed in pediatric and adult patients by 3 months (IQR, 1-9 months) and 6 months (IQR, 1-24 months), respectively. Adults were more likely to present with strictures (P < .001) and require bowel surgery (P < .001).…”
Section: Delay In Diagnosis Leads To Adverse Outcomesmentioning
confidence: 97%
“…Delay in diagnosis is more common in CD than UC (median delay, 7.6 months; interquartile range [IQR], 3.1-15.0 months and 3.3 months; IQR, 1.9-7.3 months, respectively; P < .001). 24 Data from the Swiss IBD cohort demonstrate that CD diagnosis can be delayed in pediatric and adult patients by 3 months (IQR, 1-9 months) and 6 months (IQR, 1-24 months), respectively. Adults were more likely to present with strictures (P < .001) and require bowel surgery (P < .001).…”
Section: Delay In Diagnosis Leads To Adverse Outcomesmentioning
confidence: 97%
“…92% of patients were diagnosed within 2 years of symptoms and 50% were diagnosed within 4 months. 20 Compared with other studies, the diagnosis delay in COPD patients was longer; it may result from that COPD was a chronic disease with a longer disease process and gradual aggravation of symptoms, while patients with other digestive diseases such as IBD often had diarrhea and blood in the stool as the rst symptoms, so they were more likely to catch symptoms early, and these symptoms were more di cult to tolerate.…”
Section: Discussionmentioning
confidence: 87%
“…In a recent retrospective study, it was found that nearly half of the liver www.nature.com/scientificreports/ cirrhosis patients delayed the diagnosis of hepatocellular carcinoma (HCC) in 60 days or more after danger signs 17 . A new study from the United Kingdom has shown that diagnostic delay may exist in patients with inflammatory bowel disease (IBD); precisely, 92% of the patients were diagnosed within 2 years of the development of the symptoms and 50% were diagnosed within 4 months 18 . The diagnostic delay in COPD patients was relatively long, which might result from COPD being a chronic disease with a longer disease process and gradual aggravation of symptoms.…”
Section: Discussionmentioning
confidence: 99%